Analisis Strategi Pemasaran Pada Gerai Transmart Carrefour Pabelan (studi kasus pada konsumen transmart carrefour pabelan) - Fiki Meliyanawati; Supawi Pawenang; Solichul Hadi (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to analyze the marketing strategy at the Prefan Carrefour Transmart outlet. This type of research uses quantitative research. The population of this study is consumers of Carrefour Pabelan Transmart outlets, samples in the study were 100 people sampling techniques using random sampling methods, data analysis techniques used this study using multiple linear regression. F test results indicate that the location, promotion and quality of service simultaneously and significantly influence the purchase decision on the Carrefour Pabelan Transmart Outlet. T test results showed thatothe location had ahpositive and significant effect on purchasing decisions at the Pabelan Carrefour Transmart Outlet, promotion hadlal positive and significant effection purchasing decisions at the Pabelan Transmart Carrefour Outlet, service quality had positive and significant effection purchasing decisions at the Prefan Carrefour Transmart Outlet. Dermination coefficient shows theolocation, promotion andiserviceiquality has an influencee of 57.5% on the purchase decision variable in the Pabelan Carrefour Transmart Outlet. Keywords: Location, Promotion, Service Quality, Purchasing Decisions